Absorption and luminescence characteristics of 5I7 ↔ 5I8 transitions of the holmium ion in Ho3+-doped aluminosilicate preforms and fibres. (27th February 2015) - Ryabochkina, P A; Chabushkin, A N; Kosolapov, A F; Kurkov, A S
Abstract: We have obtained the spectral dependences of the absorption cross sections for the Ho 3+ 5 I8 → 5 I6 and 5 I8 → 5 I7 transitions in Ho 3+ -doped aluminosilicate fibres and the spectral dependence of the stimulated emission cross section for the Ho 3+ 5 I7 → 5 I8 laser transition in Ho 3+ -doped aluminosilicate fibre preforms. The lifetime of the Ho 3+ 5 I7 upper laser level in the preforms has been determined.